2001
DOI: 10.1152/jappl.2001.90.6.2411
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of low energy laser irradiation on infarction and reperfusion injury in the rat heart

Abstract: Low-energy laser irradiation (LELI) has been found to modulate biological processes. The present study investigated the effect of LELI on infarct size after chronic myocardial infarction (MI) and ischemia-reperfusion injury in rats. The left anterior descending (LAD) coronary artery was ligated in 83 rats to create MI or ischemia-reperfusion injury. The hearts of the laser-irradiated (LI) rats received irradiation after LAD coronary artery occlusion and 3 days post-MI. At 14, 21, and 45 days post-LAD coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 36 publications
(47 reference statements)
5
67
0
5
Order By: Relevance
“…Thus, it may be postulated that even when the contralateral side to the stroke is irradiated at an optimal power density of 7.5 mW/cm 2 and the ischemic zone to suboptimal energy, the overall beneficial biological effect is evident. Indeed it has been shown previously that LLLT applied to the ischemic heart was beneficial when the entire lateral part (and not only the ischemic infracted zone) of the heart was irradiated by the laser [6][7][8]. Furthermore, it has been shown in non-ischemic skeletal muscles that there was a significant upregulation of antioxidant and heat shock proteins (neuroprotective molecules) by LLLT at similar power density and wavelength to the laser used in the present study [13].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, it may be postulated that even when the contralateral side to the stroke is irradiated at an optimal power density of 7.5 mW/cm 2 and the ischemic zone to suboptimal energy, the overall beneficial biological effect is evident. Indeed it has been shown previously that LLLT applied to the ischemic heart was beneficial when the entire lateral part (and not only the ischemic infracted zone) of the heart was irradiated by the laser [6][7][8]. Furthermore, it has been shown in non-ischemic skeletal muscles that there was a significant upregulation of antioxidant and heat shock proteins (neuroprotective molecules) by LLLT at similar power density and wavelength to the laser used in the present study [13].…”
Section: Discussionsupporting
confidence: 62%
“…In an experimental model of the infarcted heart it was previously demonstrated that LLLT had a profound cardioprotective effect, resulting in a 50-70% reduction in infarct size 4-6 weeks post left descending coronary artery chronic occlusion. This phenomenon was partially attributed to a significant increase in the number of undamaged mitochondria and ATP content, as well as inducible heat shock proteins and catalase (in the serum) in infarcted laserirradiated rats and dogs as compared to non-irradiated ones [5][6][7][8]. LLLT has also been shown to biomodulate processes in the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Low-level laser therapy (LLLT) has been investigated as an alternative treatment for stroke, and LLLT has been shown to have a neuroprotective effect, 38,39 while regulating several biological processes. [40][41][42] Light can penetrate several tissues, including both the scalp and skull, and reach into the brain.…”
Section: Mechanisms Of Tllltmentioning
confidence: 99%
“…The beneficial effect of LLLT has been revealed in the infarcted heart model of rat and dogs, which showed reduction of 50-70% of infarct size in 4-6 weeks post-infarction (Oron et al, 2001a;Oron et al, 2001b;Yaakobi et al, 2001). A study by Tuby et al (2006) irradiated the heart with LLLT in both intact and post infarction rats.…”
Section: Pre-conditioning With Lllt Reduces Damage After Heart Attackmentioning
confidence: 99%